Tổng hợp và nghiên cứu phức chất hỗn hợp kim loại [Zn2BaL2(OAc)2] với phối tử N', N', N''', N''' - tetraetyl-N,N''-pyridin -2,6 - dicacbonylbis(thioure) (H2L) - Định, Lê Cảnh; Nguyệt, Triệu Thị; Mai, Trương Thị Cảm; Huy, Nguyễn Hùng (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: